Effect of Angiotensin receptor blockade on Plasma Osmolality and Neurohumoral Responses to High Environmental Temperature in Rats Fed a High Salt Diet (Nigerian Journal of Physiological Sciences, 2021)
Plasma osmolality (pOsmol) and neurohumoral signals play important roles in the pathophysiology of cardiovascular diseases. Our study investigated the effect of high environmental temperature (HET) on neurohumoral responses and pOsmol in rats fed a high salt diet (HSD), with and without angiotensin II receptor blockade (ARB), using telmisartan.  Fifty-six male 8-week old Sprague-Dawley rats (95-110g) were randomly assigned into seven groups of 8 rats. These included control rats (I) fed with 0.3% NaCl diet (normal diet, ND); salt-loaded rats (II) fed with 8% NaCl (high salt) diet; ND rats (III) exposed to HET (38.5±0.5oC ) 4 hours daily per week; rats (IV) fed with 8% NaCl diet and exposed to HET daily. Others included rats (V) fed with 8% NaCl diet and treated with telmisartan (30mg/kg); ND rats (VI) exposed to HET and treated with telmisartan; rats (VI) fed with 8% NaCl diet, exposed to HET and treated with telmisartan. Plasma angiotensin II, aldosterone, vasopressin and norepinephrine (NE) concentrations were determined by ELISA technique; pOsmol from plasma K+, Na+ and Urea. HSD combined with HET in rats synergistically increased pOsmol (P